Parental attachment, inter-parental conflict and late adolescent's self-efficacy - Parsa, Nakisa; Yaacob, Siti Nor; Redzuan, Ma'rof; Parsa, Parisa; Esmaeili, Nooshin Sabour (Canadian Center of Science and Education, 2014)
The main purpose of this study was to determine the relationship between parental attachment, inter-parental conflict and self-efficacy among 374 college students aged 17 to 19 years old in Iran. The probability proportional to size sampling technique was used to obtain sample size. The Inventory of Parent and Peer Attachment, the Children’s Perception of Inter-parental Conflict Scale, and the General Self-Efficacy Scale were used to measure parental attachment, inter-parental conflict and self-efficacy, respectively. Results of Pearson correlation coefficient showed that parental attachment was positively and inter-parental conflict was negatively associated with adolescent’s self-efficacy.